A descriptive cost‐analysis of MYX.1/MCRN003, a phase 2 clinical trial evaluating high‐dose weekly carfilzomib, cyclophosphamide, and dexamethasone in relapsed and refractory multiple myeloma. (23rd June 2021) - Monteith, Bethany E.; Venner, Christopher P.; Cheung, Matthew C.; Pater, Joe; Shepherd, Lois; Richardson, Harriet; Reece, Donna; Gul, Engin; Lalancette, Marc; Castonguay, Vincent; Kukreti, Vishal; Tiedemann, Rodger; et al.
Abstract: Background: The prevalence of multiple myeloma is increasing and there is a need to evaluate escalating therapy costs (Canadian Cancer Statistics A, 2020). The MYX.1 phase II trial showed that high‐dose weekly carfilzomib, cyclophosphamide, and dexamethasone (wKCD) is efficacious in relapsed and refractory disease. We conducted a descriptive cost analysis, from the perspective of the Canadian public healthcare system, using trial data. Methods: The primary outcome was the mean total cost per patient. Resource utilization data were collected from all 75 trial patients over a trial time horizon. Costs are presented in Canadian dollars (2020). Results: The cost of treatment was calculated from the time of patient (pt) enrollment until the second data lock. The mean total cost was $203 336.08/pt (range $17 891.27‐$505 583.55) Canadian dollars (CAD, where 1 CAD = 0.67 Euro (EUR)) and $14 081.45/pt per cycle. The median number of cycles was 15. The predominant cost driver was the cost of chemotherapy accounting for an average of $179 332.78/pt or $12 419.17/pt per cycle. Carfilzomib acquisition accounted for the majority of chemotherapy costs – $162 471.65/pt or $11 251.50/pt per cycle. Fifty‐six percent (56%) of patients had at least one hospitalization during the trial period with an average cost of $12 657.86 per hospitalization. Three patients developed thrombotic microangiopathy (TMA) with an average cost of $18 863.32/pt including the cost of hospitalizations and therapeutic plasma exchange. Conclusions: High‐dose wKCD is an active triplet regimen for relapsed and refractory multiple myeloma (RRMM) associated with reduced total cost compared with twice‐weekly carfilzomib‐based regimens.